2009
DOI: 10.1097/pas.0b013e31818af361
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evidence for Progression of Microglandular Adenosis (MGA) to Invasive Carcinoma

Abstract: Microglandular adenosis (MGA) is an uncommon, benign breast lesion that is characterized by a proliferation of small uniform, round glands lined by a single layer of epithelial cells around open lumina with haphazard infiltrative growth in fibrous and fatty breast tissue. Although MGA usually has an indolent course, there is morphologic evidence that MGA can be a precursor for the development of intraductal and invasive ductal carcinoma. To investigate the possibility of such a transition, we studied 17 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
68
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 22 publications
18
68
2
1
Order By: Relevance
“…The majority of invasive cancers developing in microglandular adenosis is of triple-negative phenotype [108][109][110][111][112] and show metaplastic elements or is of adenoid cystic morphology. [109][110][111][112] It has been recently shown that microglandular adenosis may be a nonobligate precursor of triple-negative and basallike breast cancers.…”
Section: Precursors Of Basal-like and Triple-negative Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of invasive cancers developing in microglandular adenosis is of triple-negative phenotype [108][109][110][111][112] and show metaplastic elements or is of adenoid cystic morphology. [109][110][111][112] It has been recently shown that microglandular adenosis may be a nonobligate precursor of triple-negative and basallike breast cancers.…”
Section: Precursors Of Basal-like and Triple-negative Cancersmentioning
confidence: 99%
“…[109][110][111][112] It has been recently shown that microglandular adenosis may be a nonobligate precursor of triple-negative and basallike breast cancers. 108,113 A stepwise progression in the number of gross chromosomal changes from microglandular adenosis to invasive carcinoma has been observed. 108 However, given the rarity of microglandular adenosis, it is unlikely to be the precursor lesion for most triple-negative cancers.…”
Section: Precursors Of Basal-like and Triple-negative Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Recently, microarray analysis on the triple negative subtype of ductal invasive carcinomas has indicated that actually there is a subset of these cases that does not express claudins. These cases were described as "claudin-low" and were characterized by statistically significantly worse prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although benign, carcinoma can arise within MGA, and there is morphologic, immunohistochemical, and molecular evidence that supports its role as a precursor lesion to some invasive triple-negative breast carcinoma. [1][2][3][4][5][6] Microglandular adenosis has been reported over a wide age range, but most cases occur in women in their 40s to 60s. 1,[7][8][9][10] It most often presents as a palpable mass, but it may also be discovered on screening imaging or as an incidental histologic finding.…”
Section: Myoepithelial-negative Small Glandular Proliferations-mga Anmentioning
confidence: 99%